Analisis Partisipasi Nasabah, Value Co-creation, dan Loyalitas Nasabah: Studi Kasus Aplikasi Mandiri Mobile Banking LIVIN - Novi Hartati; Mariana Simanjuntak (BADAN PENERBIT STIEPARI PRESS, 2024)
This research focuses on three types of values that are co-created: comfort value, economic value, and relational value. This study uses a quantitative approach with a survey method. The results of the study show that customer participation has the greatest impact on economic value and also has a significant impact on the value of pleasure. These created values affect system satisfaction, which in turn increases customer loyalty and overall company satisfaction. Thus, the company's strategy in increasing customer happiness and loyalty through self-service technology is highly dependent on the active participation of customers in the creation of shared value.